Cassius Dio on Septimius Severus’ decennalia and ludi saeculares - Scott, Andrew G. (Histos, 2017)
The epitome of Cassius Dio’s book 77[76] contains a description of various celebrations that took place in 202–4 CE. The lack of clarity in this passage has led scholars to attribute certain spectacles to the wrong celebrations and to posit various hypotheses about the nature of the epitome of this section of Dio’s history. This paper suggests that Dio intentionally conflated the celebrations of these years into one passage, which functions as part of his narrative of the rise and fall of Plautianus and calls into question the public image of the house of Septimius Severus at this time.